Distribution of SMI-32-immunoreactive neurons in the central auditory system of the rat - Ouda, Ladislav; Druga, Rastislav; Syka, Josef (Brain structure & function, 2012)
SMI-32 antibody recognizes a non-phosphorylated epitope of neurofilament proteins, which are thought to be necessary for the maintenance of large neurons with highly myelinated processes. We investigated the distribution and quantity of SMI-32-immunoreactive(-ir) neurons in individual parts of the rat auditory system. SMI-32-ir neurons were present in all auditory structures; however, in most regions they constituted only a minority of all neurons (10-30%). In the cochlear nuclei, a higher occurrence of SMI-32-ir neurons was found in the ventral cochlear nucleus. Within the superior olivary complex, SMI-32-ir cells were particularly abundant in the medial nucleus of the trapezoid body (MNTB), the only auditory region where SMI-32-ir neurons constituted an absolute majority of all neurons. In the inferior colliculus, a region with the highest total number of neurons among the rat auditory subcortical structures, the percentage of SMI-32-ir cells was, in contrast to the MNTB, very low. In the medial geniculate body, SMI-32-ir neurons were prevalent in the ventral division. At the cortical level, SMI-32-ir neurons were found mainly in layers III, V and VI. Within the auditory cortex, it was possible to distinguish the Te1, Te2 and Te3 areas on the basis of the variable numerical density and volumes of SMI-32-ir neurons, especially when the pyramidal cells of layer V were taken into account. SMI-32-ir neurons apparently form a representative subpopulation of neurons in all parts of the rat central auditory system and may belong to both the inhibitory and excitatory systems, depending on the particular brain region.
Keywords: Inferior Colliculi; colliculus inferior; Analysis of Variance; monoklonální protilátky; přední mozek; sluchové korové centrum; Cochlear Nucleus; Rats, Long-Evans; Microscopy; imunohistochemie; sluchová dráha; Neurofilament Proteins; krysa rodu Rattus; Neurons, Afferent; Animals; mikroskopie; analýza rozptylu; Auditory Cortex; Immunohistochemistry; zvířata; Prosencephalon; Rats; Auditory Pathways; nucleus cochlearis; Antibodies, Monoclonal; metathalamus; neurony aferentní; potkani Long-Evans; Geniculate Bodies; neurofilamentové proteiny